(untitled) (DAPesquisa, 2021)
The present article reflects on the production of garments for adolescents with morbid obesity from 12 to 14 years of age, in view of the growing number of users in the condition of being overweight and the way brands make their fashion products. The objective is to broaden the debate on the beauty standards of the fashion market, in addition to asking if the clothing offered caters to the teenagers in question. The method used was a bibliographic review on the social space of children and adolescents over the centuries, a study on social practices as the arbiter of the notion of beauty and self-care, in addition to a field research that covered the application of a questionnaire to a group of teenagers and their guardians at Pedro Ernesto Hospital, in the nucleus dedicated to adolescent health, NESA. Interviews were also carried out with professionals who took care of the girls’ health, and with the owners of two clothing brands that would be related to those studied. We end with a reflection on the professional practice of the Designer within the capitalist mode of production, and the labor activity of designing clothes for users. The research is relevant for inviting peers to reflect on the established standards of beauty and production, which materialized in the way they are making clothing products, according to the material conditions of production, do not serve the users in question.